Multicomponent Synthesis of Unsymmetrical Unsaturated N‐Heterocyclic Carbene Precursors and Their Related Transition‐Metal Complexes1. Issue 52 (4th December 2013) - Queval, Pierre; Jahier, Claire; Rouen, Mathieu; Artur, Isabelle; Legeay, Jean‐Christophe; Falivene, Laura; Toupet, Loic; Crévisy, Christophe; Cavallo, Luigi; Baslé, Olivier; Mauduit, Marc
Abstract A low‐cost, modular, and easily scalable multicomponent procedure affording access in good yields and excellent selectivity (up to 93 %) to a wide range of (a)chiral unsymmetrical 1‐aryl‐3‐cycloalkyl‐imidazolium salts is disclosed. Electronic and steric properties of the corresponding unsymmetrical unsaturated N‐heterocyclic carbene (U2‐NHC) ligands were evaluated and evidenced strong electron donor ability, high steric discrimination, and modular steric demand.